The use of extended-release tacrolimus twice a day might be beneficial for selected kidney transplant recipients: a case report - Füessl, Louise; Kreuzer, Lena; Nierychlewski, Kajetan; Seibt, Tobias; Stangl, Manfred Johannes; Koliogiannis, Dionysios; Meiser, Bruno; Schwarz, Markus; Fischereder, Michael; Kemmner, Stephan (Frontiers in Medicine, 2024)
The calcineurin inhibitor tacrolimus, which is available as immediate-or extended-release formulation is the standard of care immunosuppression after kidney transplantation with low rejection rates especially in the first year after transplantation. However, its highly variable metabolism rate, narrow therapeutic window and nephrotoxic side effects requires close drug monitoring and individual dosing. Here we describe first the application of extended-release tacrolimus (ER-Tac) twice daily with beneficial effects in a kidney transplant recipient under extensive therapeutic drug monitoring. A 47-year-old female kidney transplant recipient, who was identified as fast metabolizer for tacrolimus, presented with declining allograft function and low tacrolimus through levels over time eight years after a second kidney transplantation despite the administration of high doses of ER-Tac once daily. Thereby, the area under the concentration time curve (AUC) showed exceedingly high blood levels of ER-Tac. Latest biopsy of the kidney transplant showed arteriolar hyalinosis with pole vessel stenosis as a sign of chronic transplant vasculopathy as well as transplant glomerulopathy as sign of chronic humoral rejection. After exclusion of other options of immunosuppressive therapy due to the patient's high immunological risk, the patient was switched from ER-Tac once daily to ER-Tac twice daily. After switching to ER-Tac twice daily, the AUC for oral tacrolimus decreased and the transplant function improved despite higher tacrolimus trough levels and a lower total dose administered.This case highlights the importance of careful therapeutic drug monitoring with performance of an AUC in the follow-up management of kidney transplant recipients.